Development of Learning Textbook Based ICT For Master’s Student of Primary Education - Hendratno, Hendratno; Yermiandhoko, Yoyok (International Journal for Educational and Vocational Studies, 2020)
This research aims to produce learning textbooks based on ITC that are suitable for master students in primary education. This research is a type of research and development, which is a research to develop a product. The subjects of the study were master's student of primary education class 2018/2019. Data collection techniques through the validation of learning textbooks based ICT, observation and tests. The results showed that 1) valid, according to expert validation ratings with valid categories, 2) practical, in accordance with the assessment of the two observers seen from increased student activity at each meeting, 3) effective, visible from the significant difference between the results of the pretest and posttest test master’s student of learning result and positive master’s student responses. Based on the results of data analysis, it can be concluded that the development of ICT-based learning textbooks based ICT is valid, practical, and effective in the use of learning for master students of primary education